For Research and Pest Management Considerations, Pear Psylla Monitoring (Texas Journal of Agriculture and Biological Sciences, 2023)
Pears are a delicious fruit with over 3000 varieties around the world. In value terms, pear production totaled $X in 2021 estimated in export price. China (X tons) constituted the largest volume of pear production, surpassing the figures recorded by the second-largest producer, the United States (X tons). The global average pear yield rose modestly to X tons per ha in 2021, picking up by 3% against 2020 figures. The most prominent rate of growth was recorded in 2016 with an increase of 6.4%. Over the period under review, the average pear yield reached the maximum level in 2021 and is likely to see steady growth in years to come. Aphids, codling moths, and pear psylla are all pests that can cause damage to pear trees. Aphids can be knocked off with water and insecticidal oils, while codling moths produce up to four generations per year and the larvae tend to cause the most damage. Pear psylla is a damaging pest that can cause rapid and total reduced tree vigor, eventually killing the tree..